Criminal and professional liability of medical professionals in Poland - present and future. - Iwona Wrześniewska-Wal; Dariusz Hajdukiewicz; Anna Augustynowicz; Lidia Janiszewska; Michał Waszkiewicz; Piotr Winciunas (Wiedza Medyczna, 2022)
The article presents criminal and professional liability that may be born by persons providing healthcare services, in particular doctors and dentists. The Act on the professions of doctor and dentist containing the basic directives for dealing with patients is of key importance from the point of view of the medical profession. Its provisions imply, first of all, doctor’s obligation to pursue his/her profession in accordance with the current state of medical knowledge, using available methods and means. The Act also establishes an obligation to observe the principles of professional ethics and to exercise due diligence in the performance of professional activities. Similar regulations apply to other medical professionals: nurses and midwives, physiotherapists, pharmacists and laboratory diagnosticians. A failure to exercise due diligence by a doctor providing medical services or by another medical professional may constitute grounds for a patient to report a suspected offence or file a complaint with the Screener for Professional Liability. The article discusses in a practical way examples of criminal and professional court rulings.